Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.


Calculate $\dfrac{1^2+2^2+3^2+4^2+\cdots+23333330^2}{1+2+3+4+\cdots+23333330}$.


I know the denominator is arithmetic series and equals $$\frac{n}{2}(T_1+T_n)=\frac{23333330}{2}(1+23333330)=272222156111115,$$ but how do I calculate the numerator without using a calculator?

share|improve this question
Do you know how to find the sum of squares? –  Calvin Lin Jul 12 at 19:34
I dunno. Can you help me Calvin? –  LLawliet Jul 12 at 19:36
Lab stated the formulas in his solution. –  Calvin Lin Jul 12 at 19:37

2 Answers 2

up vote 8 down vote accepted

Intuitively, \begin{align} S_1&=\frac{1^2}{1}=1=\frac{3}{3}\\ S_2&=\frac{1^2+2^2}{1+2}=\frac{5}{3}\\ S_3&=\frac{1^2+2^2+3^2}{1+2+3}=\frac{7}{3}\\ S_4&=\frac{1^2+2^2+3^2+4^2}{1+2+3+4}=3=\frac{9}{3}\\ \vdots\\ \large\color{blue}{S_n}&\color{blue}{=\frac{2n+1}{3}}. \end{align}

share|improve this answer
This solution appears to be more elegant than others! –  MonK Jul 12 at 20:09
This is smart way. Genius! (y)(y) –  LLawliet Jul 12 at 20:10

$$S_1=\sum_{r=1}^nr =\frac{n(n+1)}2$$

and $$S_2=\sum_{r=1}^nr^2=\frac{n(n+1)(2n+1)}6$$

So, the ratio $\dfrac{S_2}{S_1}$ should not demand calculator

share|improve this answer
What do you think the OP learned from seeing this? One more formula to be memorized? –  Jyrki Lahtonen Jul 12 at 19:38
How to get the formula sum of squares? –  LLawliet Jul 12 at 19:42
@doank: when search $S_2(n)$ as polynomial $S_2(n)=an^3+bn^2+cn$ (due to intuition :), then $$S_2(n)-S_2(n-1) = n^2$$ can help here. –  Oleg567 Jul 12 at 19:46
@doank,$$S_2(n)= 1^2+2^2+\ldots+(n-1)^2+n^2,$$ $$S_2(n-1)= 1^2+2^2+\ldots+(n-1)^2,$$ so $$S_2(n) = S_2(n-1)+n^2,\tag{1}$$ or $$S_2(n)-S_2(n-1) = n^2,\tag{2}$$ Now, if you'll search $S(n)$ as $$S(n)=an^3+bn^2+cn,$$ ($S(0)=0$, so last term "$+d$" is void), then $(2) \Rightarrow$ $$ an^3+bn^2+cn - a(n-1)^3 - b(n-1)^2-c(n-1)=n^2; $$ $$ an^3+bn^2+cn - a(n^3-3n^2+3n-1) -b(n^2-2n+1)-c(n-1)=n^2; $$ $$ 3a n^2 +(-3a+2b)n + (a-b+c)=n^2; $$ so $$ 3a=1;\\ -3a+2b=0;\\ a-b+c=0; $$ and hence we can find $a=\dfrac{1}{3}$, $b=\dfrac{1}{2}$, $c=\dfrac{1}{6}$. –  Oleg567 Jul 12 at 20:48

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.